Effectiveness of Injectable Alendronat for Bone Defect due to Osteoporosis - Aniek Setiya Budiatin; Cantika Suci Adlina Lasandara; Junaidi Khotib; Samirah Samirah (Humanistic Network for Science and Technology (HNST), 2019)
Alendronate is a drug of the bisphosphonate group used for the treatment and prevention of osteoporosis in postmenopausal women. However, when given orally, alendronate can cause indigestion and osteonecrosis of the jaw. It also has a poor bioavailability. Taking these disadvantages into account, an injection formulation of alendronate was created in this study to act on the site locally. Beside alendronate, the injection also contains bovine hydroxyapatite and gelatin as alendronate carriers. Both, besides being able to act as carriers, are also able to reduce bone damage caused by osteoporosis. The aim of this study was to determine the effectiveness of alendronate injection for fractures caused by osteoporosis in mouse models that were ovariectomized. The parameters used in this study were ALP concentration in blood and bone radiology. The results of ALP concentration showed that there were no significant differences in each group. The average ALP concentration of the negative control group was 277.67 ± 46.090, in the positive control group 270.33 ± 189.716, in the BHA-Gel group 406.33 ± 212.547 and in the BHA-Gel Alendronate group 325.00 ± 73.750. Bone radiology results and macroscopic observations still showed bone defects in each group.Yet in the negative control group, the BHAGel-Alendronate group and the BHA-Gel group, bone defects were almost entirely ameliorated. On the contrary, bone defects were still present in the positive control group. Based on the results obtained, it was shown that the injection of alendronate has not been shown to significantly overcome osteoporosis fractures. Keywords: Osteoporosis, Alendronate, Ovariectomy, Bovine hydroxyapatite, Gelatin